Psychological Impact On Victims of Sexual Violence: Literature Review - Byba Melda Suhita; Novita Ratih; Kurniawan Edi Priyanto (Universitas STRADA Indonesia, 2021)
Sexual violence is an act that leads to sexuality towards someone that is carried out by force, by anyone regardless of the relationship with the victim both in the family and work environment which can have a psychological impact on the victim. The literature study aims to determine the psychological impact experienced by each victim of sexual violence. In this literature study using five databases with the majority of research designs using case-control and qualitative. Prisms are used to select studies which include journals for the last five years and in English and Indonesian, titles, and abstracts. From the search results, eleven journals that match the inclusion criteria were obtained and the average number of participants was more than one hundred in each study. The psychological impact of sexual violence obtained from the summary of several studies is anxiety, withdrawal behavior, trauma, depression, and suicidal ideation